Aging and biological rhythms - Karasek, Michał (Menopause Review/Przegląd Menopauzalny, 2006)
Circadian rhythmicity in many important physiological functions plays an important role in the maintenance of proper function of the body as a whole. However, advanced age is characterized by deterioration of many circadian rhythms (e.g. sleep/wake cycle, the core body temperature, and secretion of many hormones), leading to disorganization of the temporal structure of the organism’s rhythmic physiology and behavior. Aging is often associated with earlier timing of endogenous circadian rhythmicity and reduced amplitude of many rhythms. Basic data concerning age-related changes in biological rhythms are presented in this survey.